Greening the System: Implementation of Green Technology in Administrative and Learning Management within Islamic Education Institutions - Miftahul Janah; Roza Ghozwatul Fauziah; Qurrotul 'Aini; Eva Varkatun Nazilah; Niken Ristianah (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
This study explores the implementation of Green Technology (Greentech) in the dual domains of administrative management and pedagogical processes within Islamic education institutions (madrasahs, Islamic schools, and pesantren). It investigates the potential of Greentech—encompassing energy-efficient hardware, paperless systems, cloud computing, digital learning platforms, and IoT-based resource monitoring—to reduce environmental impact while enhancing operational efficiency and learning outcomes. Employing a mixed-methods sequential explanatory design, the research first surveyed a broad sample of institutions to map adoption levels, followed by in-depth case studies of early adopters. Findings indicate significant potential for reducing carbon footprint and operational costs through virtualization of services, e-learning integration, and smart facility management. However, major challenges persist, including high initial investment, digital literacy gaps among educators, concerns over technology's influence on traditional Islamic pedagogy (talaqqi), and inadequate technological infrastructure. The study concludes that a strategic, values-driven approach aligning Greentech adoption with maqashid sharia (particularly hifdz al-mal/resource preservation) is crucial. It presents a phased integration model that prioritizes technologies offering both environmental and educational benefits, advocating for a balanced fusion of technological efficiency and the preservation of relational, character-based Islamic learning.